A conceptual hybrid project management model for construction projects - Lalmi, Abdallah; Fernandes, Gabriela; Souad, Sassi Boudemagh (Procedia computer science, 2021)
The commonly adopted project management approach is the traditional plan-driven model, which sometimes is not the most appropriate approach to complex construction projects subject to successive changes, where more agile approaches might be more adequate. The objective of this paper is to provide a hybrid project management approach that not only draws on traditional project management approaches, but also on agile and lean ones, and that seeks to promote change, boost interaction with the client and increase project value, by using the agile approach component to increase the probability of success of construction projects; and to eliminate waste by embodying the lean approach component. The paper thoroughly reviews the available literature on different project management approaches and proposes a hybrid project management model for construction projects, presenting and discussing key traditional, agile and lean practices.